The fiscal channel of monetary policy - Max Breitenlechner; Martin Geiger; Mathias Klein (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
This paper empirically quantifies the importance of fiscal policy in shaping the monetary policy transmission mechanism and derives implications for monetary-fiscal interactions. First, we document that a contractionary monetary policy shock, besides lowering output and prices, leads to a pronounced adjustment in fiscal measures and a significant increase in the fiscal deficit. We then construct different structural counterfactuals, in which we shut down the endogenous responses of fiscal measures following a monetary policy shock. The impact of a monetary policy shock on output is more than halved by the endogenous adjustment in tax revenues, whereas the public transfer system significantly reduces the impact on prices. Thus, the tax system considerably improves the trade-off between price and output stabilization the central bank faces, whereas the transfer system worsens it. Finally, we show that changes in the fiscal framework can enhance monetary policy effectiveness.
Keywords: E32; E52; E63; 330; Monetary policy; fiscal channel; monetary fiscal policy interaction; structural counterfactuals; Bayesian proxy structural VAR models